A mapping review on safety culture in Malaysian industries: a research report from 2007 to 2022 - Rahim, Hafiz; Che Dom, Nazri; Dapari, Rahmat; Precha, Nopadol (UMT Press, 2023)
Optimising a companys safety culture is a tool for reducing and preventing workplace accidents. However, the variables that affect safety culture across industries have not been thoroughly studied and are rarely discussed in previous research. The objective of this study is to identify the factors that affect a companys safety culture across industries in Malaysia over the past decade. In this systematic review study, the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method was used. The Scopus and Web of Science databases were used for these qualitative studies, which identified seven industries engaged in safety culture research between 2007 and 2022. The research found that behavioural factors were the most important aspect of safety culture, followed by situational and psychological factors. Nineteen elements of safety culture and three main research objectives of safety culture in different industries were identified within the study period. In addition, a different preference of the elements of safety culture was found in different industries in Malaysia. In conclusion, a systematic review study provides researchers, companies, practitioners, and policy makers with a snapshot of the Malaysian safety culture landscape and the elements preferred by different industries to reduce occupational accidents in the future.